Arbuscular mycorrhizal fungi associated with adaptive plants in gold mine tailing - Faisal Danu Tuheteru; HUSNA; ALBASRI; ASRIANTI ARIF; SUTRI AYU WULAN; KARTINI KRAMADIBRATA (Biodiversitas Journal of Biological Diversity, 2019)
Abstract. Tuheteru FD, Husna, Albasri, Arif A, Wulan SA, Kramadibrata K. 2019. Arbuscular mycorrhizal fungi associated with adaptive plants in gold mine tailing. Biodiversitas 20: 3398-3404. Arbuscular mycorrhizal fungi (AMF) are fungi from division Glomeremycota within the kingdom Fungi, which have a broad ecological range and symbiosis with a variety of vegetations, including vegetations in gold post-mining areas or gold tailings. The study of identifying types of AMF in gold tailings in Southeast Sulawesi is still limited. The purpose of this study was to identify the types of AMF in the rhizosphere of adaptive plants in gold tailings land in Bombana District, Southeast Sulawesi. Soil samples were collected from adaptive plants in Perseroan Terbatas (PT) Panca Logam Makmur, Bombana District, Southeast Sulawesi Province, Indonesia. AM Fungi spores were isolated and identified based on their morphological characteristics (shape, size, color, attached hyphae, and spore ornamentation). Five types of AMF were identified, namely Glomus aggregatum, Sclerocystis sinuosa, Acaulospora scrobiculata, A. tuberculata, Scutellospora pellucida, and two genera that had not been identified up to species, Glomus sp. and Scutellospora sp. In addition to spores, the symbiosis of AM Fungi with adaptive plants was also demonstrated by the structure of AM Fungi in plant roots with a rate of 74% colonization. S. pellucida and S. sinuosa were recorded as new species in Indonesia and Sulawesi, respectively. While A. tuberculata is a type of AMF that enriches AMF diversity in Southeast Sulawesi.